129Xe chemical shift in human blood and pulmonary blood oxygenation measurement in humans using hyperpolarized 129Xe NMR. Issue 4 (8th April 2016) - Norquay, Graham; Leung, General; Stewart, Neil J.; Wolber, Jan; Wild, Jim M.
Abstract : Purpose: To evaluate the dependency of the 129 Xe‐red blood cell (RBC) chemical shift on blood oxygenation, and to use this relation for noninvasive measurement of pulmonary blood oxygenation in vivo with hyperpolarized 129 Xe NMR. Methods: Hyperpolarized 129 Xe was equilibrated with blood samples of varying oxygenation in vitro, and NMR was performed at 1.5 T and 3 T. Dynamic in vivo NMR during breath hold apnea was performed at 3 T on two healthy volunteers following inhalation of hyperpolarized 129 Xe. Results: The 129 Xe chemical shift in RBCs was found to increase nonlinearly with blood oxygenation at 1.5 T and 3 T. During breath hold apnea, the 129 Xe chemical shift in RBCs exhibited a periodic time modulation and showed a net decrease in chemical shift of ∼1 ppm over a 35 s breath hold, corresponding to a decrease of 7–10 % in RBC oxygenation. The 129 Xe‐RBC signal amplitude showed a modulation with the same frequency as the 129 Xe‐RBC chemical shift. Conclusion: The feasibility of using the 129 Xe‐RBC chemical shift to measure pulmonary blood oxygenation in vivo has been demonstrated. Correlation between 129 Xe‐RBC signal and 129 Xe‐RBC chemical shift modulations in the lung warrants further investigation, with the aim to better quantify temporal blood oxygenation changes in the cardiopulmonary vascular circuit. Magn Reson Med 77:1399–1408, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.